Driving Purchasing Decisions: Digital Marketing, Brand Image, and Store Atmosphere at Gazebo Jamur: Pengaruh Pemasaran Digital, Citra Merek, dan Atmosfer Toko terhadap Keputusan Pembelian: Studi Kasus di Gazebo Jamur Sidoarjo - Rachma Annisa Firdaus; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2022)
This study aimed to investigate the influence of digital marketing, brand image, and store atmosphere on purchasing decisions at Gazebo Jamur, a restaurant in Sidoarjo. A quantitative research approach was employed, utilizing a non-probability sampling method called purposive sampling. The sample consisted of 100 respondents who had purchased and dined at Gazebo Jamur. Data analysis was performed using multiple linear regression through SPSS version 25. The findings revealed significant effects of digital marketing, brand image, and store atmosphere on purchasing decisions at Gazebo Jamur. These results highlight the importance of these factors in shaping consumer behavior and emphasize the need for businesses to strategically manage their digital marketing efforts, maintain a positive brand image, and create an inviting store atmosphere to enhance purchasing decisions. Highlights: The study examines the impact of digital marketing, brand image, and store atmosphere on purchasing decisions at Gazebo Jamur in Sidoarjo. The research employs a quantitative approach with 100 respondents using purposive sampling. Results indicate significant effects of digital marketing, brand image, and store atmosphere on purchasing decisions, emphasizing the importance of these factors for businesses in shaping consumer behavior. Keywords: Digital marketing, Brand image, Store atmosphere, Purchase decisions, Gazebo Jamur.